Implementation of Ethno-Ergonomics through the Synergy of Dewata Nawa Sanga Manifestations to Improve Physiological Stability and Health (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Ethno-ergonomics is a branch of health science that discusses the physiology of work that considers human abilities, capabilities, and limitations and their implementation according to certain community groups. Dewata Nawa Sanga are nine Gods with their respective characteristics. The characteristics of the nine Gods are synergized with the anatomical and physiological conditions of humans related to their health. The method used is through a quasi-experimental. The research design uses a randomized pre and post test group design involving 32 subjects. The research process is: identification of problems, prioritization of problems, and formulation of an action plan. The independent variable, the implementation of ethno-ergonomics through the synergy of the manifestation of Dewata Nawa Sanga and the dependent variables: (1) understanding and caring attitude towards the management of physiological conditions and (2) health quality seen from musculoskeletal complaints, fatigue, and stress due to work. The data obtained were analyzed descriptively by looking for the percentage of change and continued with a paired t-test at a significance level of 5%. The results showed an increase in: (a) physiological stability as seen from a 27.87% decrease in musculoskeletal complaints, a 24.88% decrease in fatigue, and a 28.42% decrease in work-related stress; (2) an increase in understanding of health governance by 17.77%; and (3) an increase in caring attitudes toward health governance by 23.93%. The conclusion is that the implementation of ethno-ergonomics through the synergy of Dewata Nawa Sanga manifestations can improve physiological stability, understanding, and the community's caring attitudes toward health governance.